Secrecy Performance for Multiple Untrusted Relay Networks Using Destination-Based Jamming with Direct Link - Moya Osorio, D. P.; Benitez Olivo, E. E. [UNESP]; Alves, H. (My University, 2018)
We propose a destination-based jamming scheme for cooperative networks with multiple untrusted amplify-and-forward relays, in which the destination operates in full-duplex mode so as to enable simultaneous reception of the information coming directly from the source and the transmission of jamming signals to the untrusted relay. An approximate analytical expression for the secrecy outage probability, under the effect of residual self-interference at the destination, is presented. The developed analysis is verified through Monte Carlo simulations.